2015
DOI: 10.5430/jnep.v6n4p84
|View full text |Cite
|
Sign up to set email alerts
|

The educational needs among obstetrical and gynecological nurses in El-Gharbia Governorate

Abstract: Obstetrical and Gynecological nursing is a healthcare profession that focuses on the care of the women and newborn, for that reason Obstetrical and Gynecological nurses (OB/GYN nurses) should be highly knowledgeable and well trained caregivers for the overall safety and well-being of women from the moment of menarche to menopause. The aim of this study was to assess the educational needs among obstetrical and gynecological nurses in Gharbia Governorate. This study followed a descriptive design. The study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
3
3
1
Order By: Relevance
“…The present study reveals that no one of the studied nurses received any special training courses related to gynecological examination. This result agrees with a study conducted by, Belal, Gaheen, Mohamed (2016). Who found that all of the studied nurses didn't receive any training courses specialized in obstetrics.…”
Section: Discussionsupporting
confidence: 92%
“…The present study reveals that no one of the studied nurses received any special training courses related to gynecological examination. This result agrees with a study conducted by, Belal, Gaheen, Mohamed (2016). Who found that all of the studied nurses didn't receive any training courses specialized in obstetrics.…”
Section: Discussionsupporting
confidence: 92%
“…The present study reveals that no one of the studied nures received any special training courses related to gynecological examination in Damietta Gavernrate . This result agree with a study conducted by, Belal, Gaheen, Mohamed in (2016). Who found that all of the studied nurses didn't recieved any training specialized in obstetrics.…”
Section: Discussionsupporting
confidence: 92%
“…This finding was dissimilar to (Belal et al, 2016) who found that more than half of the studied sample attended training courses about postpartum nursing care this may be related to the different characteristics of the study subjects.…”
Section: Thecontrasting
confidence: 99%